2013
DOI: 10.1016/j.jaci.2013.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Environmental assessment and exposure reduction of cockroaches: A practice parameter

Abstract: This parameter was developed by the Joint Task Force on Practice Parameters, representing the American Academy of Allergy, Asthma & Immunology (AAAAI); the American College of Allergy, Asthma & Immunology (ACAAI); and the joint Council of Allergy, Asthma & Immunology. The AAAAI and the ACAAI have jointly accepted responsibility for establishing “Environmental assessment and remediation: a practice parameter.” This is a complete and comprehensive document at the current time. The medical environment is a changi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 100 publications
(108 reference statements)
0
63
0
1
Order By: Relevance
“…17 Portnoy et al recently developed a practice parameter for assessment of environmental cockroach exposure and methods for allergen reduction and avoidance. 18 Mouse allergen has also been found to be prevalent in both urban homes and schools with home mouse allergen levels associated with cockroach infestation. 19, 20 Home exposure to mouse allergen in the inner-city has been associated with increased asthma morbidity.…”
Section: Allergic Rhinitis and Environmental Allergen Exposurementioning
confidence: 99%
“…17 Portnoy et al recently developed a practice parameter for assessment of environmental cockroach exposure and methods for allergen reduction and avoidance. 18 Mouse allergen has also been found to be prevalent in both urban homes and schools with home mouse allergen levels associated with cockroach infestation. 19, 20 Home exposure to mouse allergen in the inner-city has been associated with increased asthma morbidity.…”
Section: Allergic Rhinitis and Environmental Allergen Exposurementioning
confidence: 99%
“…Cat litter boxes have also been hypothesized as sources of moisture capable of supporting fungal growth (O'Connor et al, 2004). The observation of cockroaches may suggest that water and moisture sources are present and sufficient to support infestation (Portnoy et al, 2013). Home crowding and lack of ventilation can contribute to condensation problems.…”
mentioning
confidence: 99%
“…As first demonstrated by the Inner City Asthma Studies (ICAS), environmental interventions designed to reduce cockroach infestation and exposure – through a combination of professional cleaning, food removal, bait traps, insecticides, and HEPA filters – can be effective in also reducing asthma symptoms [184]. Other studies have subsequently shown 80–90% reductions in cockroach allergen levels through Integrated Pest Management (IPM) techniques [7, 184189], and some recent studies have even suggested that comparable reductions can be achieved through the strategic placement of bait traps alone, with associated improvements in asthma morbidity [190, 191]. …”
Section: Bedroom Allergen Exposuresmentioning
confidence: 99%